INCREASING THE CARRYING CAPACITY OF REINFORCED CONCRETE DRIVEN PILES BY CHANGING THEIR CROSS SECTIONAL GEOMETRY - Darwish, Ala’a M. (European Scientific Journal, ESJ, 2014)
The ultimate carrying capacity of a reinforced concrete driven pile is mainly obtained by calculating the product of its surface area multiplied by the adhesion stress between its shaft and the surrounding soil. For a certain type of soil its average frictional stress with concrete surfaces is taken equal to its value at mid depth of the pile. The surface area of a pile is the product of its cross sectional circumference multiplied by its length. Through this study it was shown that the circumference of a circular cross section is less by 13% compared to the circumference of an equivalent area square section. A suggested star cross section has been investigated; it was shown that it has an increase of 25% in its circumference compared to a square cross section having a similar area. By adapting the suggested star shape cross section driven pile, it is believed that its carrying capacity will be more than that of a square cross section pile by 25%. In other words; to develop the same required carrying capacity of a group of piles, the suggested star shape cross section driven piles can be driven to four fifths of the required depth of the current similar area square cross sectional piles.